Autoriti sanad tarekat dan peranannya dalam ilmu tasawuf - Faudzinaim Badaruddin,; Muhammad Khairi Mahyuddin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sanad or silsilah in Sufism occupies an important place in the practice of sufi path (tariqah). It forms as a basic element wherein the practice of sufi path is built upon. The sanad of sufi path refers to the chain transmission which shows a continuous spiritual chain which provides a connection of a sufi teacher to a list of his shuyukh or predecessors. It occupies an important position in the sufi path. Nonetheless, the existent of sufi sanad has been challenged and its validity has been compared to a sanad in hadith transmission. Hence, this article aims to give an explanation on the existent and validity of chain of transmission of sufi sanad and to provide an exposition of its statue and its roles in practical sufism. The writing of this article used a document analysis as its method of collecting data and analysed using a descriptive analysis. This article shows that the sanad of sufi path stands as an integral part of religion itself. It has its authority within the Islamic spiritual culture and plays an important role in an organized tariqah as providing a standard of legitimization and recognition of a sufi to become a teacher or spiritual guide to sufi aspirants.